The role of national culture in financial innovation and bank stability transmission - Edward Marfo-Yiadom; George Tweneboah (Cogent Economics & Finance, 2022)
This paper examines the role of national culture in the transmission process through which the growth in credit to the private sector can lead to bank stability in 107 countries over 2005 and 2017. We performed the examination using the quantile regression and the dynamic generalised method of moment to explore asymmetry properties in the panel dataset and address endogeneity challenges that can affect the efficiency of the results. We found that national culture dimensions influence the impact of financial innovation on bank stability. On the specific effect of national culture, we found that higher levels of indulgence and long-term orientation serve as a substitute for financial innovation in promoting bank stability. Higher levels of individuality and masculinity have no effects on the impact of financial innovation on bank stability. Higher power distance and uncertainty avoidance complement the relationship between financial innovation and bank stability. Finally, countries with lower levels of indulgence and long-term orientation can increase access to bank credit to boost banking system stability. The implication is that regulators should consider the cultural orientation of their communities in promoting sound financial intermediation.
Keywords: 330; Financial innovation; national culture; bank stability